Math Learning Problematics on the Subject of 3D Topics - Narimoati, Hega; Fitriani, Annisa; Alfiyansah, Ahmad Faris; `Handayani, Meli (Proceeding International Conference on Science and Engineering, 2020)
In the 21st century, the ability to be mastered by students is increasingly complex, such as the ability of critical thinking, creative thinking skills, communication skills, ability to cooperate, as well as ability in reasoning. The ability of reasoning in students is crucial to learn and develop. The reasoned ability is not only needed when studying mathematics but is indispensable when determining decisions in life. The instrument in this study is how the mathematical reasoning process of students is low, moderate and high on the subject matter of three dimensions. The study aims to know students' learning difficulties relating to the students' mathematical reasoning ability on surface area material and the volume of three-dimensional space. This research is a qualitative descriptive study with a case study approach. The subject of this study involved 30 students. The instrument in this research is a mathematical reasoning ability test. The results showed that 40% of students had high reasoning ability, 40% of students had moderate reasoning ability, and 20% had low reasoning ability. Students with high reasoning ability have no significant difficulty in completing the instrument in this study, students with reasoning ability are having difficulty in calculating and interpreting the intent of the question, and students with low reasoning ability have difficulty in drafting a completion plan. The study concluded that the students' reasoning ability on the three-dimensional material belongs to the medium category.